Situating subsidiarity - Barber, N; Ekins, R (Oxford University Press, 2016)
Subsidiarity is a principle about the ordering of relations between groups. It has a foothold in legal doctrine, most notably in the law of the European Union, but increasingly also in international human rights law. But subsidiarity is at its heart a moral principle about how state and society (and perhaps states and societies plural) should be structured. While its precise content and implications in a range of contexts are certainly contested, at its core the principle requires higher (larger) groups to aid lower (smaller) groups, rather than to obliterate or subsume them. The principle thus recognises the value of a plurality of social groups, of multiple associations in which a measure of self-government is possible.